2007
DOI: 10.1055/s-2007-981467
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin is a Useful Alternative to Sedation in Children Undergoing Brainstem Audiometry with an Age Dependent Success Rate - A Field Report of 250 Investigations

Abstract: Though brainstem audiometry is one of the most important investigations in pediatric audiology, it often necessitates sedation or general anaesthetics, especially in newborns and infants. Melatonin, inducing natural sleep without the risks of sedation, has been successfully used to induce sleep prior to EEG investigations. 250 children (142 male, 108 female) with suspected hearing loss underwent ABR (auditory brainstem responses) tests in melatonin-induced sleep. Click-induced and notched-noise ABR tests were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 9 publications
(15 reference statements)
4
31
3
1
Order By: Relevance
“…This indicated that reliable and valid ABR could be recorded under both test conditions; which was a positive finding in the current study indicating that melatonin did not induce negative effects on morphology, repeatability and amplitudes of ABR in compliant adults with normal hearing. These findings exclude melatonin from pharmacological agents which are reported to affect the ABR 9 and support findings by Schmidt et al 8 which show that melatonin does not negatively affect the ABR waveform. To ensure reliability of these findings, a randomized double blind analysis strategy was adopted; and an independent rater was also utilized to establish Cohen's kappa (inter-rater agreement).…”
Section: Results Of the Abr Testingsupporting
confidence: 91%
See 4 more Smart Citations
“…This indicated that reliable and valid ABR could be recorded under both test conditions; which was a positive finding in the current study indicating that melatonin did not induce negative effects on morphology, repeatability and amplitudes of ABR in compliant adults with normal hearing. These findings exclude melatonin from pharmacological agents which are reported to affect the ABR 9 and support findings by Schmidt et al 8 which show that melatonin does not negatively affect the ABR waveform. To ensure reliability of these findings, a randomized double blind analysis strategy was adopted; and an independent rater was also utilized to establish Cohen's kappa (inter-rater agreement).…”
Section: Results Of the Abr Testingsupporting
confidence: 91%
“…24 Audiologically, the use of melatonin was explored in 250 children with suspected hearing loss in Germany. 8 In that study, findings indicated that melatonininduced sleep is appropriate for the completion of ABR recordings in the paediatric population; whilst simultaneously eliminating the medical risks of conventional sedatives. The current study aimed to explore this and examine possible effects on the ABR response as well.…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations